2016
DOI: 10.1371/journal.pone.0168079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sublethal Fungicides on Mutation Rates and Genomic Variation in Fungal Plant Pathogen, Sclerotinia sclerotiorum

Abstract: Pathogen exposure to sublethal doses of fungicides may result in mutations that may represent an important and largely overlooked mechanism of introducing new genetic variation into strictly clonal populations, including acquisition of fungicide resistance. We tested this hypothesis using the clonal plant pathogen, Sclerotinia sclerotiorum. Nine susceptible isolates were exposed independently to five commercial fungicides with different modes of action: boscalid (respiration inhibitor), iprodione (unclear mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…A study of the pathogen Sclerotinia sclerotiorum demonstrated that with a sublethal fungicide selection pressure, estimated mutation rates in six microsatellite markers were 1.7-to 60-fold higher than expected under neutral conditions (Amaradasa and Everhart 2016). Field 2 was maintained using conventional practices (fungicidetreated seed, in-furrow fungicide applications for pocket rot control, and two to three foliar fungicides applications [Reiners et al 2017]) and it may be expected that a subset of the field population would be exposed to sublethal fungicide levels.…”
Section: Discussionmentioning
confidence: 94%
“…A study of the pathogen Sclerotinia sclerotiorum demonstrated that with a sublethal fungicide selection pressure, estimated mutation rates in six microsatellite markers were 1.7-to 60-fold higher than expected under neutral conditions (Amaradasa and Everhart 2016). Field 2 was maintained using conventional practices (fungicidetreated seed, in-furrow fungicide applications for pocket rot control, and two to three foliar fungicides applications [Reiners et al 2017]) and it may be expected that a subset of the field population would be exposed to sublethal fungicide levels.…”
Section: Discussionmentioning
confidence: 94%
“…Current methods to control S . sclerotiorum infection involve the application of broad-spectrum fungicides, which have been attributed to the rise of chemical resistance and may have deleterious or unwanted effects on the surrounding agro-ecological landscape, if managed poorly 3 5 . Other practices, such as crop rotations, can be ineffective due to the formation of overwintering structures, termed sclerotia, which can remain in the soil for several years 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Here, consistent patterns among strains are lacking: of the five strains backgrounds that were exposed to a subinhibitory level of fluconazole, no significant changes were observed among replicates from three of them (A1, A12, A18), MIC 50 decreased in all replicates from one replicate (A20) , and variable, yet numerically significant, changes occured in replicates of another strain (A5). This variability in phenotypic outcomes is reminiscent of the case in Sclerotinia sclerotiorum, a plant pathogenic fungus, where both MIC increases and decreases (and no change) were observed and no consistent relationship was found between the change in resistance and exposure to sublethal concentrations of five different antifungal drugs (67) . Fungal strains exposed to subinhibitory drug levels thus seem less likely than bacteria to gain an advantage at higher drug levels.…”
Section: Discussionmentioning
confidence: 97%